Efforts to Increase Learning Activity and Achievement Healthy Theme is Important Through The Method Discovery Learning for Class V Students SD Negeri 3 Belikurip Semester I 2018/2019 Academic Year - Yarni, Yarni (Universitas Sebelas Maret, 2020)
This study aims to increase the activeness and learning achievement of the important healthy theme through the discovery learning method in fifth grade students of SD Negeri 3 Belikurip Semester I of the 2018/2019 academic year. The data in this study were obtained from the results of interviews, questionnaires, results of action observations, and evaluation results. This research was conducted in two cycles. Each cycle is carried out based on the stages: preparing an activity plan, carrying out actions, observing, and analyzing followed by reflection. After taking action, it is proven that the percentage of completeness of student learning outcomes is increasing. In the first cycle of the first meeting the percentage of student learning completeness reached 60%, at the second meeting it was 100% complete. The similarities of the research carried out were increasing the use of the same methods and subjects while the differences were motivation and the class being researched. Learning became fun. so that students do not get bored easily.